2018
DOI: 10.1111/acfi.12415
|View full text |Cite
|
Sign up to set email alerts
|

Institutional ownership, cross‐shareholdings and corporate cash reserves in Japan

Abstract: Cross-country studies document a negative relation between corporate governance and cash holdings. In contrast, this relation is found to be positive in the United States. In this paper, we examine the case of Japanese firms. Using institutional ownership and cross-shareholdings as the main governance variables, we show that better governance is associated with higher cash balances as in the United States. The reason is that better-governed firms make better investment decisions. Their investments are not driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 104 publications
1
10
0
Order By: Relevance
“…For example, larger, more profitable and more mature firms as well as firms with higher leverage are less likely to hoard cash. Instead, the presence of financial analysts and institutional investors tends to induce firms to increase their cash holdings (Loncan, 2020; Nguyen & Rahman, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…For example, larger, more profitable and more mature firms as well as firms with higher leverage are less likely to hoard cash. Instead, the presence of financial analysts and institutional investors tends to induce firms to increase their cash holdings (Loncan, 2020; Nguyen & Rahman, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The authors' empirical evidence showed that institutional ownership reduces the positive relationship between principalprincipal conflicts and cash holdings. Nguyen and Rahman (2020) point out that better governance increases cash holdings. The authors claim that companies with better governance have better investment decisions because they do not depend on excess liquidity.…”
Section: Institutional Ownership and Cash Holdingsmentioning
confidence: 99%
“…Corporate governance quality influences firms' cash holding behavior (Al-Najjar & Clark, 2017;Al-Hadi et al, 2020). Family, local, and foreign institutional ownership are corporate governance indicators, and there is diversified evidence about the ownership structure's effect on the firm's cash holdings behavior (Liu, 2011;Chang et al, 2014, Nguyen & Rahman, 2020 . Finance policies like dividend payment (Harford et al, 2008;Moin et al, 2020) and capital expenditures (Aǧca & Mozumdar, 2008) also affect a company's cash holdings.…”
Section: Introductionmentioning
confidence: 99%
“…The members of the board might have to make strategic decisions that involve changes on liquidity when short-term payment commitments might not be met due to lack of cash resources resulting in the deferral of payments to creditors that worsen future credit terms (Bibi and Amjad, 2017). By contrast, excess liquidity (that is, liquidity beyond the level that maximizes the firm's value) may arise with managerial entrenchment, when aiming to reduce the risk of the firm's assets to maximize the value of their human capital (Nguyen and Rahman, 2020) or in firms that do not pay dividends (Subrahmanyam et al, 2017). Therefore, changes in liquidity suggests defensive strategic moves made under financial pressure and/or a change in a firm's financial resource allocation profile.…”
Section: Liquiditymentioning
confidence: 99%